Orientation and Ordering in Sequence- and Length-Mismatched Surface-Bound DNA Hybrids - Howell, Caitlin; Jeyachandran, Yekkoni Lakshmanan; Kölsch, Patrick; Zharnikov, Michael (The journal of physical chemistry. C, Energy, materials, and catalysis, 2012)
The effects of target sequence mismatches and target length mismatches on the orientation and ordering of surface-bound, poly(dT)·poly(dA) hybrids on gold were investigated using a combination of high-resolution X-ray photoelectron spectroscopy and near-edge X-ray absorption fine structure spectroscopy. It was found that the overall orientation of the probe and target strands remained upright and relatively unchanged despite the presence of up to four sequence mismatches in the target strands, although the total number of hybrids decreased with higher numbers of mismatches. Upright probes were also observed in hybrids formed with targets of shorter length, with a greater number of hybrids present in these films as compared to those formed with longer targets. These results suggest that in DNA films of relatively high densities, such as those tested here, the presence of sequence or length mismatches in target strands does not result in a large disruption of orientation and ordering in surface-bound hybrids. This finding may be useful for those seeking to maintain consistent DNA strand orientation for precise nanotechnological applications or those using DNA microarrays for biosensing purposes.